Epidemiological aspects and oral implications of Paracoccidioidomycosis infection: an integrative review - Duarte, Ana Vitória Machado; Rodrigues, Ana Beatriz da Silva; Oliveira, Giovana Gisele Costa; Sá, Isadora de Oliveira; Prá, Jassana de Andrade Lissa Dal; Bezerra, José Vinícius de Moura; Borges, Júlia Maria de Sá; Honorato, Laís Brito; Silva, Laíza da Cruz Pereira da; Sousa, Lívia Feitosa de; Almeida, Luiza Gabriela Cardoso de; Araújo, Maria Amanda Cordeiro; et al. (Brazilian Journal of Implantology and Health Sciences, 2023)
Paracoccidioidomycosis (PCM) is a systemic mycosis caused by the dimorphic fungus Paracoccidioides brasiliensis. It represents a significant infection in South America, occurring mainly in tropical and subtropical countries such as Brazil. Oral mucosal lesions, which are the most important symptom in dentistry, may be the first visible physical manifestation of the disease, often preceding even pulmonary lesions. This study aims to carry out an integrative literature review to identify the main epidemiological aspects and oral implications of Paracoccidioidomycosis (PMC) infection. A search was carried out in the PubMed, LILACS and SciELO databases and, after applying the inclusion, exclusion, eligibility and thematic relevance criteria, 18 articles were selected for analysis in this study. Paracoccidioidomycosis (PCM) is endemic in Brazil and mainly affects middle-aged and elderly men and occurs in rural areas. It is a systemic disease where clinical manifestations are often added to oral lesions. Dentists play a key role in identifying these lesions, in the correct diagnosis and treatment of this disease. Making PCM notification compulsory in Brazil is essential.